(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: The English novel, as a literary form, has seen remarkable evolution, growing from its early experimental origins to a well-defined genre with lasting impact on culture and society. This article explores the development of the English novel from its roots in the early 18th century with writers like Daniel Defoe to the mature works of Charles Dickens in the 19th century. By examining thematic shifts, narrative techniques, and social critiques embedded in the works of these authors, we see how the English novel responded to, and helped shape its historical context.